High sensitive and direct fluorescence detection of single viral DNA sequences by integration of double strand probes onto microgels particles. Issue 4 (7th January 2016) - Aliberti, A.; Cusano, A. M.; Battista, E.; Causa, F.; Netti, P. A.
Abstract : A novel class of probes for fluorescence detection was developed and combined to microgel particles for a high sensitive fluorescence detection of nucleic acids. Abstract : A novel class of probes for fluorescence detection was developed and combined to microgel particles for a high sensitive fluorescence detection of nucleic acids. A double strand probe with an optimized fluorescent–quencher couple was designed for the detection of different lengths of nucleic acids (39 nt and 100 nt). Such probe proved efficient in target detection in different contests and specific even in presence of serum proteins. The conjugation of double strand probes onto polymeric microgels allows for a sensitive detection of DNA sequences from HIV, HCV and SARS corona viruses with a LOD of 1.4 fM, 3.7 fM and 1.4 fM, respectively, and with a dynamic range of 10 −9 –10 −15 M. Such combination enhances the sensitivity of the detection of almost five orders of magnitude when compared to the only probe. The proposed platform based on the integration of innovative double strand probe into microgels particles represents an attractive alternative to conventional sensitive DNA detection technologies that rely on amplifications methods.